2013
DOI: 10.1186/1869-5760-3-66
|View full text |Cite
|
Sign up to set email alerts
|

Candida dubliniensis endophthalmitis: five cases over 15 years

Abstract: BackgroundRecent studies have shown that the recently identified organism Candida dubliniensis is less pathogenic than the more common Candida albicans. Due to its rare nature, C. dubliniensis has been previously reported as the causative organism in endophthalmitis in only three cases. We undertook a multicenter, retrospective, consecutive case series to describe the clinical features and outcomes of patients with culture-proven C. dubliniensis endophthalmitis. Medical records were reviewed for all patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…in their study of the role of calcineurin in C. dubliniensis virulence actually created a mouse model of fungal keratitis where they demonstrated that C. albicans could cause infection in immunocompetent mouse corneas while C. dubliniensis could not and could only cause infection in the corneas of immunocompromised mice [ 12 ]. This is further supported by case series of endogenous endophthalmitis where visual outcomes have been shown to be better with C. dubliniensis as compared to C. albicans [ 5 ].…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…in their study of the role of calcineurin in C. dubliniensis virulence actually created a mouse model of fungal keratitis where they demonstrated that C. albicans could cause infection in immunocompetent mouse corneas while C. dubliniensis could not and could only cause infection in the corneas of immunocompromised mice [ 12 ]. This is further supported by case series of endogenous endophthalmitis where visual outcomes have been shown to be better with C. dubliniensis as compared to C. albicans [ 5 ].…”
Section: Discussionmentioning
confidence: 81%
“…In the ophthalmology literature, C. dubliniensis was first described as a cause of fungal dacryocystitis [ 13 ] but has more recently been described as an emerging cause of endophthalmitis [ [2] , [3] , [4] , [5] , [6] , [7] ]. It has specifically been linked to several cases of endogenous endophthalmitis in IV drug users [ [3] , [4] , [5] , [6] ]. In fact, one such case was recently identified and treated at our institution by our retina colleagues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C. albicans has been the predominant species isolated and C. dubliniensis is a rare cause [5]. C. dublinensis had been generally considered less virulent than C. albicans as it is susceptible to environmental stressors and produces less hyphae in-vitro than C. albicans [6,7]. Disputing this are increasing reports on infections caused by C. dubliniensis that have hypothesized increased neutrophil migration, phagocytosis, cytokine release and ineffective interleukin-17A production by peripheral blood mononuclear cells as possible reasons [4,8].…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis and rapid aggressive antifungal therapy are important to reduce ocular complications such as blindness. Diagnosis is often based on clinical findings documented by dilated eye exam and work up should be directed to identify the source [1,2,6]. The intraocular inflammation in fungal endophthalmitis tends to occur in “clumps” within the aqueous and/or vitreous (Fig.…”
Section: Discussionmentioning
confidence: 99%